HUBUNGAN BODY IMAGE DENGAN POLA MAKAN PADA REMAJA PUTRI - Tan, Cindy Carlin; Ibrahim, Ibrahim (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2020)
Nowadays, society still has standard that beautiful women are slim ones. Presumption of an ideal body image usually triggers teenage girls to do everything to reach this standard. It makes teenagers follow diet and other efforts to pursue a thin body that leads to malnutrition caused by an unhealthy diet. The purpose of this research was to find out the correlation between body image and diet. This research used a cross sectional method that conducted in Senior High School and samples of this research were 87 students. It used Simple Random Sampling Technique. Researcher used chi square test to analyze the data to find out the correlation between variables assisted by SPSS program. The result of this research showed that teenage girls who have Negative Body Image and Good Diet were 8 respondents (17.8%) and negative Body Image and Bad Diet were 37 respondents (82.2%). Statistical test results showed that there was a correlation between body image and diet (p=0.00). In conclusion, more than half of respondents had a negative body image because they were not confident with their appearance and followed diet to lose their weight so it impacted to their eating patterns. It is suggested for Senior High School to conduct healthy diet counseling.